Surface modification of PVA hydrogel membranes with carboxybetaine methacrylate via PET-RAFT for anti-fouling. (24th January 2019) - Lin, Yanming; Wang, Ling; Zhou, Jinsheng; Ye, Lin; Hu, Huiyuan; Luo, Zhongkuan; Zhou, Li
Abstract: In this study, we grafted brush-like CBMA copolymer brushes onto the surface of PVA hydrogel membrane through photo-induced electron transfer–reversible addition fragmentation chain transfer (PET-RAFT) polymerization. ATR-FTIR, XPS, AFM, UV–Vis absorption spectra and elemental analysis were adopted to characterize the hydrogels, and equilibrium swelling, water contact angle, vitro cytotoxicity assay, protein adsorption and cells adhesion experiments were used to evaluate the related property of hydrogels. The results of ATR-FTIR and XPS showed that pCBMA was successfully grafted onto the surface of PVA hydrogel membrane. The Ra roughness of hydrogel surface in AFM increased slightly from 5.44 nm to 6.12 nm. Transmittance of the PVA-g-pCBMA hydrogel in the visible range (380 nm-780 nm) was remaining at 91.2%–97.0%. The optimal reaction conditions (CPADB: 1.20 mmol/L, Eosin Y: 0.03 mmol/L and CBMA: 358 mmol/L) were confirmed through control experiments. The equilibrium swelling and water contact angle showed that the swelling ratio increased from 2.06 cm 3  g −1 to 3.65 cm 3  g −1, while the water contact angle decreased from 45.94° to 18.06° with the increase of grafting ratio (23.92%–55.18%). In vitro cytotoxicity assay by CCK-8 showed that the cells relative viability remained at least 90.55%. Anti-protein adsorption experiment illustrated approximately 57.2% improvement of anti-protein capacity at 37 °C, while cells adhesion experiment also showed about 64.57% improvement of anti-cells capacity. These results revealed the applicability of the oxygen tolerant PET-RAFT mechanism on the PVA modification and it was effective, feasible and non-cytotoxic method to prepare the other functional PVA hydrogel membrane. Graphical abstract: Image 1 Highlights: The PET-RAFT is first used in surface modification of PVA hydrogel membrane and it has a large industrial application potential. We use a low-cost organic dyes Eosin Y as photoredox catalyst and investigated some PET-RAFT reaction factors to research the reaction mechanism. We obtained the relationship of grafting ratio and the weight of elements. We synthesized a kind of zwitterionic--- Carboxybetaine Methacrylate(CBMA). We further enhanced the anti-fouling capacity of PVA hydrogel membrane via pCBMA grafting.